The chosen - Potok, Chaim (Simon & Schuster Paperbacks, 2022)
"It's the spring of 1944 and fifteen-year-olds Reuven Malter and Danny Saunders have lived five blocks apart all their lives. But they've never met, not until the day an accident at a softball game sparks an unlikely friendship. Soon these two boys -- one expected to become a Hasidic rebbe, the other at ease with secular America -- are drawn into each other's world despite a father's strong opposition. Set against the backdrop of World War II and the creation of the State of Israel, The Chosen is a poignant novel about transformation and tradition, growing up and growing wise, and finding yourself-- even if it might mean disappointing those you love" --